3 - Pathways out of Commercial Sexual Exploitation of Children: The Dissonance Between Interventions and Social Norms: Rejoice Makaudze, Eliot Tofa & Tichavona Mushonga - Makaudze, Rejoice (Africa Development, 2022)
The fight against the commercial sexual exploitation of children (CSEC) in Zimbabwe has tended to focus on the need to enact and effectively implement laws, policies and programmes. While these interventions are important, negative norms and attitudes towards children who are victims of CSE continue to be embedded in the Zimbabwean society. This study examines how the dissonance between legal and formal institutions on the one hand and social norms and attitudes towards CSEC on the other undermines interventions against CSEC. This is because in order to be effective; laws, policies, programmes and institutions need to largely emerge from and be consistent with society’s underpinning relationships, aspirations and norms. The fight against CSEC in Zimbabwe can take a meaningful trajectory if these negative norms and attitudes towards children who are victims of CSE are transformed.